2023
DOI: 10.22201/ib.20078706e.2023.94.5028
|View full text |Cite
|
Sign up to set email alerts
|

Luciérnagas (Coleoptera: Lampyridae) del norte-occidente de México, con la descripción de 48 especies nuevas

Abstract: Se sintetiza la información de luciérnagas de la región norte-occidente de México, que abarca los estados de Baja California, Baja California Sur, Sonora, Chihuahua, Coahuila, Nuevo León, Sinaloa, Durango, Zacatecas, San Luis Potosí, Nayarit, Jalisco, Aguascalientes, Guanajuato, Querétaro, Colima y Michoacán. Se comentan 67 especies de las 69 registradas, que corresponden a los géneros Ankonophallus Zaragoza-Caballero y Navarrete-Heredia, 2014 (2), Aspisoma Laporte, 1833 (4), Aspisomoides Zaragoza-Caballero, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
7
0
6
Order By: Relevance
“… * New records for Morelia. ** New records for Michoacán, mainly based on Zaragoza-Caballero et al (2020 , 2023 ) and Pérez-Hernández, Zaragoza-Caballero & Romo-Galicia (2022) . …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… * New records for Morelia. ** New records for Michoacán, mainly based on Zaragoza-Caballero et al (2020 , 2023 ) and Pérez-Hernández, Zaragoza-Caballero & Romo-Galicia (2022) . …”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies, a total of six genera and 16 firefly species had been reported in Michoacán state ( Pérez-Hernández, Zaragoza-Caballero & Romo-Galicia, 2022 ); later six new Photinus species were described by Zaragoza-Caballero et al (2023) . According to our findings, the species list for Michoacán now contains at least nine genera ( Cratomorphus and Pyractomena as new records) and 41 species (at least 14 new records for the state; Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations